Political Landscapes of Capital Cities (University Press of Colorado, 2016)
"[Political Landscapes of Capital Cities] is a welcome contribution to the study of the spatialization of society and suggests paths that anthropologists can take to analyze political space in urban and non-urban settings alike." —Anthropology Review Database